Lier récits de vie et récits historiques - Irène Dos Santos (Conserveries Mémorielles)
In Portugal, until recently, the official memory of the Empire has overlooked the violent pasts under the dictatorship and decolonization – colonial war, repatriation - less unifying for the national collective identity. The first part of this article focuses on the societal and academic shift resulting from the emergence of memorializing counter-narratives. The aim is to identify the players in these processes and illustrate how, in this new political relationship with the past, the memory of dictatorship can be imbricated with that of decolonization. Studying current research — historiography, postcolonial studies — also highlights divergences in Portuguese academia on the role of history and memory — postmemory in particular — in the interpretation of such past events. The second part looks back on two case studies with a heuristic potential to deconstruct the very homogeneous representations of the history of Portuguese colonization and decolonization of Angola, and decompartmentalize national accounts. This relates to two individuals whose family histories link them to the Portuguese colonial presence in Angola, involved in writing about the past through eye-witness accounts or scientific research: an exiled in France, grandson of a colonial administrator and son of an anticolonial and antifascist militant actions; and the daughter of an interracial couple of retornados undertaking research on Angola. These case studies also reveal the complexity of social, political and ethno-racial affiliations in this postcolonial post-imperial context and challenge the social hierarchization inherited from the past and the silence surrounding this heritage.